(untitled) (Journal of the College of Basic Education, 2022)
The architecture folklore considers a total production extended for long continues year of technology , developed and practiced by the Arab craftsmen and architecturs , to from the bace of our architectural history in the most highness and complicated architecture and arts forms and florishing within the conduct of the civilized development . this production aspirated in the cities ,palaces ,mosques in the Abbasside century which expreced directly of that architectural implementation so in this study we saw that it was useful to explin the elected samples of what they obtain of high imazing engineering architecture , but only a humble participation to emerge a scientific facts deals with the phenomena of aesthetics fitness through studying al- Malwiya Minaret , Therefor , the researchers see itis necessary to reveal the flowing question : 1-what is the aesthetics of fitness in the Malwiya Minarets? The imprical from of the second chapter included three parts ; the first was about the fitness in the Malwiya Minarets and the mathematical engineering sense which links the illusion and sense with an engineering harmony to participat in connecting ideas with the engineering and mathematical findings in creating forms through aesthetics sense and harmony abilities . While the second part included acquiring al- Masjed al – Jamaa in samaraa a distinguished position among the ancient Iraqi mosques and also among the masques of the Islamic world , and it is unique in its area and the only one in its greatness in building . it is also famous with its malwiya minaret which is distinguishable by its from , greatness and hight . The third part dealt with abi – dalaph malwiya which depended basically on the spiral alivating stairs , to imphasis on achieving the aesthetics experience through the conscious in space formating , then discussing what had said in the imprical form ; while the third chapter ,was including the proceedurs of the research , and the forth chapter included conclusions , proposals , and recommendations .